Impact behaviour of composite plate with embedded piezoelectric sensor - Dezfouli, Mohammad Mehdi Salehi (2011)
In engineering sciences, control and maintenance of the composite structures against environmental impacts is very important. Sensors are used for identifying impact location on the composite structures. Piezoelectric sensors are applied in two forms; bonded (on the composite) and embedded (in the composite) for identifying impact location. Regarding to importance of embedding the sensors in the composite plate, in this study, at first, a PZT sensor (PIC155) was embedded in four layers of woven fibre glass using cut-out method. For evaluating behaviour of the output voltage versus distance of impact point from the sensor, many points on the composite plate were impacted and the output voltage was detected. Three samples were fabricated in this study. Sample 1 included a PZT sensor and four layers of fibreglass in which all the fibres of layers were parallel (0/90/90/0). Sample 2 included a PZT sensor and four layers of fibre glass in which fibres of the first and the forth layers (bottom and top of the plate) made an angle of 45o with fibres of second and third layers (45/90/90/45). Results of impact tests on sample 1 showed for the points by the minimum distance (10mm) from PZT sensor the maximum voltage (5.7 V), and for the points by the maximum distance (60mm) from PZT sensor the minimum voltage (0.96 V) was gained. Results of impact tests on sample 2 showed for the points by the minimum distance (10mm) from PZT sensor the maximum voltage (8.7 V), and for the points by the maximum distance (60mm) from PZT sensor the minimum voltage (3.5 V) was gained. Therefore, the output voltage of the sensor had indirect relation with distance of the impact point from the sensor. When the impact point distance from sensors increased, the output voltage decreased. The difference of output voltage between sample 1, and sample 2 was because of different velocity of wave propagation in sample 1 (c1=1058.78 m/s) and sample 2 (c2=1745.87 m/s) caused by deferent orientation of sample 1 (0/90/90/0) and sample 2 (45/90/90/45). For identifying impact location on the composite plate with a PZT Patch, impact happened on the random points of the composite, and the locus of the impact point was identified by output voltage. The locus of the impact was a circle that R was radius and sensor was the centre. It should be mentioned that R was calculated by output voltage. Sample 3 included two PZT sensors and four fibre glass layers (orientations of the third sample was the same as the second sample). For identifying impact location using two sensors, output voltages of the sensors were analysed. Results of impact tests on sample 3 showed when the impact point distance from sensor 1 increases (from 2 to 12 cm), and from sensor 2 (from 12 to 2cm) decreases, V1 decreases (from 7.98 to 0.8 V), and V2 increases (from 0.72 to 7.6 V), respectively. Results showed that the locus of the impact point was crossing points of the two circles with radii R1 and R2. R1 and R2 were calculated by output voltages. Therefore, by supposing one of the two sensors as the origin of the Cartesian coordinate, the impact location can be identified.